Complémentarité de la recherche et des actions de terrain. Le travail de prévention VIH et d’accès aux droits avec les personnes prostituées - Florence Garcia (Tracés, 2009)
Cabiria is a community health association which works with prostitutes and regularly welcomes migrant sex workers. Research programs conducted by Cabiria focus on the reality of these women’s histories, who are often considered as victims of slave trade. The programs offer a more complex view of these histories, showing how women develop strategies and a form of autonomy throughout their lives.